2012
DOI: 10.1037/a0026355
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and its relationship to emotional regulation.

Abstract: Research on the effectiveness and mechanisms of mindfulness training applied in psychotherapy is still in its infancy (Erisman & Roemer, 2010). For instance, little is known about the extent and processes through which mindfulness practice improves emotion regulation. This experience sampling study assessed the relationship between mindfulness, emotion differentiation, emotion lability, and emotional difficulties. Young adult participants reported their current emotional experiences 6 times per day during 1 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
277
2
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 444 publications
(333 citation statements)
references
References 53 publications
23
277
2
11
Order By: Relevance
“…Previous research has demonstrated a significant relationship between mindfulness and a construct termed emotion regulation (e.g., Hill & Updegraff, 2012). Emotion regulation has been defined as the ability to reduce or control negative emotions (Erisman & Roemer, 2010).…”
Section: Mindfulness and Emotion Regulationmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has demonstrated a significant relationship between mindfulness and a construct termed emotion regulation (e.g., Hill & Updegraff, 2012). Emotion regulation has been defined as the ability to reduce or control negative emotions (Erisman & Roemer, 2010).…”
Section: Mindfulness and Emotion Regulationmentioning
confidence: 99%
“…Emotions varied on the dimension of pleasantness-unpleasantness (e.g., positive emotions: happy, content, peaceful; negative emotions: sad, ashamed, nervous) and participants rated their experience of these emotions 1 (not at all) to 7 (a great deal). Hill and Updegraff (2012) considered higher correlations between the Palm Pilot ratings of similarly valenced emotions to reflect lower differentiation; thus, they defined emotion differentiation as the ability to distinguish between similarly valenced emotions (i.e., ratings of the individual's experience of similarly valenced emotions, such as "happy" and "content", would differ). The researchers found that emotion differentiation mediated the relationship between mindfulness and emotion lability.…”
Section: Mindfulness and Emotion Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…These are: (1) focused attention or concentration, accompanied by tranquility, relaxation, a decrease in anxiety and worries, greater (emotional) stability and joy; (2) open-monitoring (mindfulness per se) with increased (interoceptive) awareness of the body, the emotions and their differentiation (Hill and Updegraff 2012), belief formation, appraisals and other cognitive practices, with concomitant increases in the adjustability and flexibility of mental processes (Shapiro et al 2006); (3) loving kindness and compassion, i.e. a transition from worrisome to loving/accepting attention, providing conditions for positive emotions and stability for psychotherapeutic working-through, and a more compassionate attitude toward life and other beings (Salzberg 2011;Neff et al 2007).…”
Section: Concepts and Mechanisms In Applying Mindfulness In Psychothementioning
confidence: 99%